(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with knowledge, attitudes, and prevention of cervical cancer among female nursing students at Thai Binh University of Medicine and Pharmacy. Research Method: A cross-sectional descriptive study was conducted on 302 nursing students at Thai Binh University of Medicine and Pharmacy in the 2022–2023 academic year. Data were collected through interviews using a questionnaire. Results: General knowledge about cervical cancer: Third-year students had a higher rate of knowledge than first and second-year students; OR = 18.7 (95%CI: 8.4 - 46.8). The group with Good/Excellent/Outstanding academic performance had greater knowledge (OR = 5.8; 95% CI: 3.4 - 9.9; p = 0.001). Having family members working in the medical field (p < 0.01) and having access to information about cervical cancer (p = 0.003) improved the knowledge attainment rate. Students with satisfactory knowledge had a 2.3 times higher rate of positive attitudes than those without satisfactory knowledge (95% CI: 1.1 - 5.6; p < 0.05). Vaccination rates were higher in the group with sufficient/excessive economic means (p < 0.05); families with family members working in the medical field (OR = 8.6; 95%CI: 3.8 - 19.4); and those with satisfactory knowledge about cervical cancer (OR = 2.3; 95%CI: 1.2 - 4.8; p = 0.01). Conclusion: Students’ knowledge about cervical cancer is positively correlated with their academic year, academic performance, and access to information. Acquired knowledge and family history among healthcare professionals are essential factors that promote positive attitudes and preventive vaccination behaviors.